The Pursuit Of Climate Protection And The Uneven Global Distribution of Clean Development Mechanism (CDM) Projects: Lesson From Least Developed Countries (LDCS) - Agbonifo, Philip (European Journal of Sustainable Development, 2017)
In this modern era of climate protection, the need for climate justice in the distribution of projects cannot be neglected or postponed. While the pursuit of climate and environmental protection, sustainable development and green technologies have become increasingly topical, issues surrounding the sustainability of the Least Developed Countries (LDCs) within the context of climate protection are being unwittingly developed and ignored. Thus, this article offers a critique of the uneven distribution of Clean Development Mechanism (CDM) projects. While most projects have gone to the emerging countries of China, India, Brazil and Mexico with opportunities for investment, unfortunately very little projects were established in the LDCs of Africa and Middle East. This prompts the question whether the CDM is fulfilling its climate protection goal, or does it currently deliver its sustainable development claim in the LDCs? Only a relatively few countries that are attractive destinations for foreign direct investment have benefited immensely from CDM projects. Consequently, this paper looks into the distribution of CDM project activities among developing countries, justification for the distribution, and examines what can be done to ensure equity among developing countries concerning the harnessing of the benefits of the CDM. Keywords: Least Developed Countries (LDCs); Clean Development Mechanism (CDM); sustainable development; climate protection; uneven project distribution.